(untitled) - Sharma, Rajeev (New Delhi, 1999)
Pakistan's attack on India at Kargil; exploitation of Muslim fundamentalist Osama Bin Laden and Inter Services Intelligence, the national security agency of Pakistan.
Keywords: Pakistan,Ấn Độ,Pakistan,India; Military relations,Quan hệ quân sự,Quan hệ quân sự,Military relations; Indiam,Pakistan,Ấn Độ,Pakistan